Ideology, Legitimation and Collective Action: Evidence from Chile on the Mechanism of Ideological Inversion. (3rd April 2022) - Puga, Ismael; Moya, Cristóbal
Abstract: We present evidence on a social mechanism of legitimation—ideological inversion—proposing that a fantasy consensus deters collective actions oriented toward social change, even in contexts were individuals support transformations. This fantasy consensus emerges as individuals infer the order's validity mainly from the practices of others, which are largely constrained by social structures. Relying on a factorial survey experiment conducted in Chile, our results support the two main hypotheses from ideological inversion: people systematically overestimate the support for the status quo, and this overestimation has a deterrent effect on collective actions oriented toward social change. We argue that ideological inversion helps explain how legitimation crises often remain hidden, and therefore how political crisis often emerge abruptly. For instance, before the revolt of 2019 Chile was perceived as an example of social stability within Latin America, yet after an ordinary subway fare hike the country erupted in an unrelenting and massive wave of protests. Our findings suggest that the social support for the status quo previously perceived in Chile was a fantasy consensus enforced by constrained practices, and that this fantasy was very effective until recently in deterring social change. Ideological inversion thus provides a mechanism that contributes to explain the stability of social structures and inequalities regardless of individual dispositions or shared norms.